The Effect of Organizational Learning on Employee Performance Through Organizational Commitment - Effendi Agung Nugroho (Syntax Corporation Indonesia, 2023)
This study aims to examine and analyze the effect of organizational learning, job satisfaction on employee performance by involving organizational commitment as a mediator variable. This research uses primary data from questionnaire processing which is distributed with the responses of 197 respondents. Data from the questionnaire were then analyzed using SEM-PLS with the help of WarpPLS 7.0 software. The sampling technique used is purposive sampling. The research results provide empirical evidence that organizational learning has no significant effect on employee performance but has a significant effect on organizational commitment, and job satisfaction has a significant effect on employee performance and job satisfaction has a significant effect on commitment. Organizational commitment has a significant effect on employee performance and organizational commitment does not mediate the relationship between organizational learning and employee performance. Organizational commitment mediates the relationship between job satisfaction and employee performance. Factors such as wage rates, career openness, career fairness, promotion opportunities, teamwork, leadership trust and good working relations in the company environment are proven to be very good constituents of job satisfaction variables that have an impact on improving employee performance.